Învăţământul profesional în sistem dual – o alternativă mai bună de intrare a tinerilor pe piaţa muncii? Școala profesională germană Kronstadt, Braşov. Studiu de caz - Naghi, Dana Ioana (Calitatea Vieții, 2016)
Qualifying human resources through practical skills training on secondary educational level is a challenge for initial vocational education and training system in the context of economic decentralization and higher education massification. Therefore, the gap between work and education, respectively, between the professional requirements and skills is the result of the lack (crisis) of jobs or the deficit (crisis) of skills? Following the same line of ideas, it is possible that these two overlapping crises to be the result of poor coordination between stakeholders involved in this problem: the education and training providers for the labor market, ministries and representatives of government administration, employers, and not least the young people. Vocational education in dual system designed on the German model, could represent an alternative to relaunch initial vocational education and training in Romania and a better solution for young people's transition towards employment. The key factor of educational dual system is the practical component on which it focuses, developing professional skills of young people directly at the workplace, the following case study aimed to look more closely in these respects, the German Vocational School “Kronstadt” from Braşov being presented as an example of good practice.